Protective immunity induced by oral immunization with a rotavirus DNA vaccine encapsulated in microparticles - Chen, S C; Jones, D H; Fynan, E F; Farrar, G H; Clegg, J C; Greenberg, H B; Herrmann, J E (Journal of virology, 1998)
DNA vaccines are usually given by intramuscular injection or by gene gun delivery of DNA-coated particles into the epidermis. Induction of mucosal immunity by targeting DNA vaccines to mucosal surfaces may offer advantages, and an oral vaccine could be effective for controlling infections of the gut mucosa. In a murine model, we obtained protective immune responses after oral immunization with a rotavirus VP6 DNA vaccine encapsulated in poly(lactide-coglycolide) (PLG) microparticles. One dose of vaccine given to BALB/c mice elicited both rotavirus-specific serum antibodies and intestinal immunoglobulin A (IgA). After challenge at 12 weeks postimmunization with homologous rotavirus, fecal rotavirus antigen was significantly reduced compared with controls. Earlier and higher fecal rotavirus-specific IgA responses were noted during the peak period of viral shedding, suggesting that protection was due to specific mucosal immune responses. The results that we obtained with PLG-encapsulated rotavirus VP6 DNA are the first to demonstrate protection against an infectious agent elicited after oral administration of a DNA vaccine.